Two consecutive pregnancies in a patient with premature ovarian insufficiency in the course of classic galactosemia and a review of the literature. (1st February 2022) - Kruszewska, Jagoda; Laudy-Wiaderny, Hanna; Krzywdzinska, Sandra; Grymowicz, Monika; Smolarczyk, Roman; Meczekalski, Blazej
Abstract: Aim: To present a case report of a patient with classic galactosemia and the Q188R/K285N GALT mutation, who conceived spontaneously twice despite severe ovarian failure. A review of the literature is included. Materials and methods: A 20-year-old patient with classic galactosemia and premature ovarian insufficiency (POI) came to our attention. We performed a routine hormonal and ultrasound examination confirming low ovarian reserve. Due to low rates of pregnancies in individuals with POI (5%–10%), we were almost certain of the infeasibility of pregnancy. Results: Surprisingly, several months after hospitalization, the patient conceived without any medical intervention and less than a year after the first birth she became pregnant again. While reviewing the literature, 90 pregnancies among galactosemic patients were identified. Conclusions: Ovarian failure is a long-term diet-independent complication of classic galactosemia, pertaining to about 90% of affected individuals. This case confirms its unpredicted course, as even the presence of unfavorable factors (absence of spontaneous puberty, early diagnosis of POI, undetectable AMH) may not preclude the chance for conception.